Light-driven N2 fixation for green NH3 production in H2-N2 energy storage systems - Filiz, Bilge Coskuner; Acikalin, Korkut; Yoruklu, Huelya Civelek; Calisan, Murat (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Ammonia (NH3) is considered the major compound for the chemical industry and energy sector as a prominent liquid medium for energy storage with its capability of storing 19.65 wt. % of its mass in hydrogen (H2). The main catalytic process of NH3 production-the Haber-Bosch process-led to massive carbon emissions globally. The global decarbonization goals have been made prominent for the improvement of the alternative renewablebased technologies and the adaptation of the green technologies. The green NH3 is going to play a critical role in shifting the classical high energy consumption and CO2 emissions industry with alternative pathways based on material science. Light-driven N2 fixation for green NH3 production based on the conversion of atmospheric N2 gas has been performed based on catalysts in several forms, such as type-1, type-2, z-scheme and heterostructure catalysts. This study aims to provide a comprehensive review of the transition from conventional NH3 production to sustainable, solar-driven N2 fixation methods. Specifically, it focuses on the development and optimization of heterojunction photocatalysts as a promising approach for carbon-neutral NH3 synthesis with low energy consumption. By leveraging photocatalytic N2 activation is inspired by biological processes, this work explores how advanced semiconductor materials and heterojunction interfaces can enhance charge separation, N2 adsorption, and overall catalytic efficiency. Furthermore, a bibliographic analysis has been conducted to identify the latest research trends, catalyst development strategies, and emerging innovations in this field.
Keywords: Hetero-junction; Catalyst; N2 fixation; Artificial solar; Ammonia; PHOTOCATALYTIC N-2 FIXATION; NITROGEN-FIXATION; CARBON NITRIDE; PHOTOFIXATION ABILITY; OXYGEN-VACANCY; CONVERSION; CHALLENGES; NANOSHEETS; REDUCTION; Chemistry; Electrochemistry; Energy & Fuels